The Role of Public Expose Press Releases in Public Relations Strategies on Social Media: A Case Study of PT Surya Semesta Internusa Tbk (SSIA) on Meta Platforms - Elvina Aulia Rahmawati; Alya Kalindari; Aryo Kusumo Wibowo; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
The rapid development of digital communication technologies has significantly transformed the practice of corporate public relations. This study aims to conceptually examine the evolving role of press releases within digital corporate communication, particularly in relation to public expose activities conducted by publicly listed companies. Using a descriptive qualitative approach (Creswell & Creswell, 2018), this research analyzes relevant academic literature and conceptual perspectives on public relations, corporate communication, and digital media environments (AgilityPR, 2025; Axios, 2024). The analysis highlights that the function of press releases has shifted from a conventional mass communication instrument toward a strategic digital communication tool that supports transparency, stakeholder engagement, and corporate reputation management (Benoit, 1995; Coombs, 2007). In the digital environment, press releases are no longer distributed solely through traditional media channels but are increasingly adapted for dissemination through social media platforms, enabling organizations to communicate directly with broader audiences (Reuters Institute for the Study of Journalism, 2025). This transformation allows corporate messages to be framed more strategically while also facilitating real-time interaction and engagement with stakeholders (Entman, 1993; Kapla & Haenlein, 2010). Furthermore, the integration of press releases with public expose communication demonstrates how digital public relations strategies can strengthen reputational signaling by presenting corporate performance, strategic direction, and organizational transparency to investors and the public (Spence, 1973; SSPACE News, 2024). The study concludes that press releases have become an integral component of holistic digital corporate communication strategies, particularly in supporting corporate disclosure practices and enhancing stakeholder trust in the contemporary digital communication ecosystem (Balmer, 2013; Smith & Taylor, 2020).